First Developments of Terminology of Mechanical Engineering in Albanian language lexical - Stojani, Edita (European Journal of Social Science Education and Research, 2023)
The purpose of this article is to present evidence of building up of terminology of Mechanical Engineering in Albanian language lexical. Mechanical Engineering of Albanian language lexical has its beginnings around the year 1910 and across the years it has been enriched with many borrowings, neologisms, and Albanian words. The borrowings in this lexical are considered as an enrichment source. The methodology used is the research and consultation of studies previously carried out by Albanian and foreign linguists, in the field of terminology, to continue with the research and analysis of how these terms have been integrated into the lexicon of the Albanian language, as well as in the collection of the corpus of Italianisms in this field, which prove the influences that the Italian language had on the Albanian language. From the analysis that was made of the lexicon of mechanics in this period, some main characteristics can be ascertained, which we are briefly discussing. First, in this lexicon, a significant number of foreign terms borrowed from different languages ??such as Italian are observed. the few attempts to create the special lexicon in the field of mechanics are permeated by the tendency to pronounce as much as possible. The linguistic borrowings, is conditioned not only by the tendency to make this lexicon as understandable as possible but also by the historical circumstances of the time.